American Predaceous Midges of the Subgenus Eukraiohelea of Stilobezzia (Diptera, Ceratopogonidae) - Wirth, Willis W. (1992)
Fil: Wirth, Willis W.. Research Associate. Florida State Collection of Arthropods. Florida; USA